2021
DOI: 10.1002/mds.28554
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of SARS‐CoV‐2 Infections in Patients with Neurodegenerative Diseases in the LEOSS Cohort

Abstract: The impact of preexisting neurodegenerative diseases on superimposed SARS-CoV-2 infections remains controversial. Here we examined the course and outcome of SARS-CoV-2 infections in patients affected by Parkinson's disease (PD) or dementia compared to matched controls without neurodegenerative diseases in the LEOSS (Lean European Open Survey on SARS-CoV-2-infected patients) cohort, a large-scale prospective multicenter cohort study. 1 The LEOSS scientific data set comprises anonymous data after data quality co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
1
12
2
1
Order By: Relevance
“…The 26 remaining factors were all measured during the critical phase of the COVID-19 disease. They included vital parameters ( 6), blood values (8), symptoms (8), and observations from CT scans (4) and are displayed in Table 2. It should be noted that for the vital parameters and blood values, the LEOSS database contains the worst measured value in the corresponding phase.…”
Section: Data Collection and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 26 remaining factors were all measured during the critical phase of the COVID-19 disease. They included vital parameters ( 6), blood values (8), symptoms (8), and observations from CT scans (4) and are displayed in Table 2. It should be noted that for the vital parameters and blood values, the LEOSS database contains the worst measured value in the corresponding phase.…”
Section: Data Collection and Patientsmentioning
confidence: 99%
“…Besides the search for factors generally associated with COVID-19, some authors focused on a specific comorbidity [3][4][5][6][7][8]. Others concentrate on demographic factors such as gender [9], ethnicity [10], or BMI [11].…”
Section: Introductionmentioning
confidence: 99%
“…Older age and male sex are important risk factors for a severe course of and/or fatality after COVID-19 infection, as are diabetes, obesity, chronic obstructive pulmonary disease, dementia, or previous neurological disease ( Williamson et al 2020;Covino et al 2020;Grasselli et al 2020;Zhou et al 2020;Bonanad et al 2020;Ko et al 2021). Pulmonary disease, obesity, and hypertension have also been specifically identified as risk factors for a severe COVID-19 disease course in PD patients (Chambergo-Michilot et al 2021;Fasano et al 2020c;Huber et al 2021). Although the risk of a complicated COVID-19 disease course is increased for people with older age and associated arterial hypertension, this risk is even higher in PD patients, especially with longer disease duration, than in non-PD patients (Fasano et al 2020b, c;Orlando et al 2021;Chambergo-Michilot et al 2021).…”
Section: Patients With Pd Are At An Increased Risk For a Complicated ...mentioning
confidence: 99%
“…A detailed review by Fearon et al summed up that COVID-19 mortality is probably not increased in PD patients who tended to experience less dyspnea during the infection, were completely asymptomatic more often and less likely to require hospitalization [ 141 , 160 , 165 , 166 , 167 ]. The duration of ICU stays/hospitalization and ventilation did also not differ in PD and non-PD COVID-19 patients in a large analysis of German inpatients [ 165 ]. An Italian study compared COVID-19 patients with PD to COVID-19 patients without PD and found no difference in mortality (5.7% of PD COVID-19 patients died vs. 7.6% of non-PD COVID-19 patients) [ 160 ].…”
Section: Chaptermentioning
confidence: 99%